PENDAMPINGAN PENGELOLAAN PERPUSTAKAAN SEKOLAH DALAM MENYAMBUT PEMBELAJARAN TATAP MUKA TERBATAS - Ramdanil Mubarok; Sitti Aisyah; Suryani PS; Rahmat Rajab; Ferdi Arinda (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
The school library is one of the essential factors in supporting limited face-to-face learning. The purpose of community service in this article is to carry out assistance in the preparation, implementation and service of the library in welcoming little face-to-face learning. The method used is an action approach method with a mentoring model so that direct service is carried out at the SMP Islam DDI Sangatta Utara Library. The result is that library management becomes more organized by creating book codes to make it easier for visitors to get the books they need. The affixing of book stamps as a sign of ownership and as a safeguard for library book collections. Making archives, visiting books and loans in an effort to control library services. It is hoped that community service can further assist technology-based library management and service systems so that management and services can be more effective and efficient.